Sound Insulation of Dwellings Façades – the Case of Santiago de Chile - MEZA, Leonardo; DELANNOY, Jaime; MARZZANO, Antonio; FUENTES, Mauricio (Archives of Acoustics, 2019)
The increment in the number of automobiles and the densification of the city has increased noise pollution rates. In addition, the lack of regulation in Chile regarding the acoustic insulation of fa¸cades is a problem of a growing concern. The main objective of the present study was to obtain a model of the Sound Insulation of housing, façades, stratified in Santiago, Chile, based on constructive variables. It is expected to serve as a basis for one future regulation for acoustic façades of houses. In the present study, tests based on the international ISO 140-5 standard were carried out in situ. An estimation model of the Standardized Level Difference Dls;2m;nT;w + C, was obtained based on the opening/façade proportion, and the type of glass used for the windows.